2020
DOI: 10.1029/2020ea001134
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Winter Haze Pollution in the Fenwei Plain and the Possible Influence of EU During 1984–2017

Abstract: During the past few years, air pollution in the Fenwei Plain (FWP) region had obviously rebounded. In this study, we used quantitative analysis, difference analysis, and correlation analysis methods to analyze the temporal and spatial distribution and the influence of the meteorological and climatic factors on haze pollution in FWP. The results showed that on the long-term timescale, the haze pollution had an overall upward trend during the winter of 1984-2017, and the pollution became more serious after 2000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…Further research and more attention are required. Nowadays, several mega urban agglomerations in China, such as the Beijing-Tianjin-Hebei region, the Yangtze River Delta region, and the Fenwei Plain, are still suffering from severe air pollution Xiang et al, 2019;Haque et al, 2020;Zhao et al, 2020). Previous studies have shown that emissionreduction strategies, which are mainly based on the results of atmospheric chemistry simulations, play an important role in reducing pollutant concentrations and improving air quality .…”
Section: Interactive Commentmentioning
confidence: 99%
See 4 more Smart Citations
“…Further research and more attention are required. Nowadays, several mega urban agglomerations in China, such as the Beijing-Tianjin-Hebei region, the Yangtze River Delta region, and the Fenwei Plain, are still suffering from severe air pollution Xiang et al, 2019;Haque et al, 2020;Zhao et al, 2020). Previous studies have shown that emissionreduction strategies, which are mainly based on the results of atmospheric chemistry simulations, play an important role in reducing pollutant concentrations and improving air quality .…”
Section: Interactive Commentmentioning
confidence: 99%
“…Printer-friendly version Discussion paper Sciences (CAMS) Zhou et al, 2008Zhou et al, , 2012Wang et al, 2010. GRAPES (Global/Regional Assimilation and PrEdiction System) is a numerical weather prediction system built by China Meteorological Administration (CMA), and it can be used as a global model (GRAPES-GFS) or as a regional mesoscale model (GRAPES-Meso) .…”
Section: Interactive Commentmentioning
confidence: 99%
See 3 more Smart Citations